MANAJEMEN DAKWAH MEDIA SOSIAL: TELAAH TERHADAP PERKEMBANGAN METODE DAKWAH ISLAM - Effendi Sadly (Universitas Islam Islam Sumatera Utara, 2018)
This study aims to describe da'wah management through social media as the development of the Islamic da'wah approach in the modern era. This is a qualitative study by collecting data from relevant literature such as books, magazines, and so on. Therefore, this type of research is called library research. The results show that mass media cannot be separated in human life moreover it is supported by technology in the communication system which is on the one hand, will be a challenge for Islamic da'wah and can be a prospect on the other side. There are at least 5 (five) kinds of influences on the development of communication technology both on da'wah actors and their da'wah partners which include economic aspects, social aspects, rescheduling, entertainment and taking part in media activities. In this sense, dakwah is required to try to make the best use of technology products. It could be using the internet and e-mail or blogs, facebook, twitter, e-mail, whatsapp, messenger, BBM, instagram, line and so on in which these facilities allow da'wah through direct interactive, question-answer session, discussion, sending messages, interfaces and communicating directly. In other words, preachers (dai) must be able to manage and at least be able to provide software for television programs for example, or films and drama so that the packaging of Islamic da'wah becomes warmer, actual, more interesting, effective and efficient.